Prevention of leg cramps by using compression stockings or magnesium supplements in the 50–84 age group: study protocol for a randomised controlled trial - Jenni Joensuu (BMC, 2021)
Abstract Background Leg cramps are painful sensations of tightening in the muscles of the legs that commonly appear during the night and are often associated with secondary insomnia. They are common especially in older age. There is no evidence that any method of prevention of nocturnal leg cramps is both safe and effective. There are no previous trials concerning cramp prevention by using compression stockings. The objective of this study is to assess in a prospective randomised controlled trial whether leg cramps can be prevented by the daily use of knee-length compression stockings or magnesium supplements. Methods The study will be set in Finland, and 50–84-year-old volunteers will be recruited through Google Ads, the Finnish health library website and Finnish primary health care centres. The participants must have a minimum of two episodes of leg cramps per week for the past 4 weeks to be included in the study. The participants (n = 225) will be allocated to three equal groups: the compression stocking arm, the magnesium supplement arm and the placebo arm. The participants will go through 4 weeks of follow-up without intervention and then another 4 weeks of follow-up with the assigned intervention. The material for the study will be collected through electronic questionnaires. Discussion This protocol describes a study that compares compression stockings, magnesium supplements and placebo for the prevention of leg cramps. The results of this study can significantly improve knowledge on the methods of preventing leg cramps. Trial registration ClinicalTrials.gov NCT04694417. Registered on Jan 4, 2021.